CRT-D implantation through a persistent left superior vena cava - Placido, Rui (2014)
Copyright © 2014 Indian Heart Rhythm Society. Production and hosting by Elsevier B.V. Production and hosting by Elsevier B.V. Open Access funded by Indian Heart Rhythm Society Under a Creative License